If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(z-7)/3=(z-6)/2
We move all terms to the left:
(z-7)/3-((z-6)/2)=0
We calculate fractions
z/()+(-((z-6)*3)/()=0
We calculate terms in parentheses: +(-((z-6)*3)/(), so:We get rid of parentheses
-((z-6)*3)/(
We multiply all the terms by the denominator
-((z-6)*3)
We calculate terms in parentheses: -((z-6)*3), so:We get rid of parentheses
(z-6)*3
We multiply parentheses
3z-18
Back to the equation:
-(3z-18)
-3z+18
Back to the equation:
+(-3z+18)
z/()-3z+18=0
We multiply all the terms by the denominator
z-3z*()+18*()=0
We add all the numbers together, and all the variables
z-3z*()=0
| 18-x=-56 | | 3(x+2)=5x-1 | | |x-2|+|x-5|=7 | | 25-9x=x+5 | | (2.5)^2x=64 | | 5(4/3)+y=7 | | 1/3b+2/3b=5/6B | | v=14+73 | | 3p-15=p+15 | | 54l+43.44=3605.26 | | 1/3b+2/3b=-5/6B= | | 1/8x+x=180 | | -2+6=-2(x-3) | | 7^m=343 | | 2x+12=12-4 | | 7m-4-2m=6A | | 3^(2x)-3^(x+1)+14=0 | | 5-3m=7m-15 | | 4x-(1/4)=8 | | X2x3=540 | | 42=y/3 | | 18 = k3+ 14 | | -22/3+x/6=2/3 | | -2x+18=12 | | 2n-7+3(4n-3)=3 | | 5x+8-x=2x+1 | | -88x=x-4x | | 85x+50=25x+70 | | z-7/3=z-6/2z= | | 1+(b-40)=4/3 | | 5e+2=2e-7 | | -r/10+5=12 |